2017
DOI: 10.1007/s00253-017-8591-z
|View full text |Cite
|
Sign up to set email alerts
|

A guard-killer phage cocktail effectively lyses the host and inhibits the development of phage-resistant strains of Escherichia coli

Abstract: In recent years, after the emergence of a large number of multidrug-resistant bacteria, phages and phage-associated products for the prevention and control of bacterial disease have revealed prominent advantages as compared with antibiotics. However, bacteria are susceptible to becoming phage-resistant, thus severely limiting the application of phage therapy. In this study, Escherichia coli cells were incubated with lytic bacteriophages to obtain mutants that were resistant to the lytic phages. Then, bacteriop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 42 publications
1
33
0
1
Order By: Relevance
“…Due to co-evolution of the phages and their host bacteria, the construction of a phage cocktail was able to avoid bacterial phage resistance [54]. Furthermore, the construction of a phage cocktail was also able to control the multiple infections caused by different bacterial pathogens [55].…”
Section: Discussionmentioning
confidence: 99%
“…Due to co-evolution of the phages and their host bacteria, the construction of a phage cocktail was able to avoid bacterial phage resistance [54]. Furthermore, the construction of a phage cocktail was also able to control the multiple infections caused by different bacterial pathogens [55].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless mutant generation by phase variation has also been shown to provide transient resistance to phage infection in case of Gram negative bacteria [40][41][42] . Different phages may recognise different kind of receptors including cell wall (mainly murein and teichoic acid), outer membrane proteins, flagellar components, pilli, lipopolysaccharides, capsular antigens or extracellular matrix structures to which they bind via adhesions or receptor binding proteins (RBPs) [43][44][45][46] . This provides us with a strategy to deal with the issue of bacterial mutants through designing phage cocktails wherein phages targeting different host receptors or phages against mutant strains are included.…”
Section: Custom Made Cocktail Designing Of Bacteriophagesmentioning
confidence: 99%
“…Conversely, phages have evolved great diversity and a multiplicity of attack mechanisms. It has been reported that the use of phage cocktails tends to slow the emergence of bacterial resistance as compared with the use of individual phages (Fischer et al 2013;Yu et al 2017). Phages act synergistically when used in cocktails (Schmerer et al 2014).…”
Section: The Challenge Of Emerging Bacterial Resistancementioning
confidence: 99%